Mindful eating for a sustainable future: predicting organic food consumption among Malaysian adults using the Theory of Planned Behaviour - Jaafar, Nur Aqilah Amalina; Sulaiman, Norhasmah; Zainal Badari, Shamsul Azahari; Sabran, Mohd Redzwan (Universiti Putra Malaysia Press, 2024)
Introduction: Safe and ecologically friendly foods are as important as nutrient-dense foods, fostering healthy lifestyles while preserving the environment. Globally, there is a shift towards organically grown food, perceived as safer and more sustainable. Yet, organic food adoption remains limited among Malaysian adults. This study explores the influencing factors of organic food consumption using the psychological theory of planned behaviour (TPB). Materials and methods: A cross-sectional survey was conducted in 2020, involving 424 Malaysian adults who were recruited through Facebook Advertisements (Ads). The ads were designed to target respondents based on age (18 years and above), geographical location (six zones of Malaysia), and interest in organic food. An online questionnaire hosted on Google Forms was embedded in the ads for data collection. The data were analyzed using descriptive analysis and structural equation modeling (SEM). Results: The study revealed that 72% of intention was explained by attitude, encompassing concern for health, food safety, and the environment, followed by perceived behavioural control and subjective norm. Actual consumption was influenced by intention, but with a small effect size, explaining 16% of the total variance. Conclusion: The structural TPB model demonstrates that attitudes, subjective norms, and perceived behavioural control significantly influence the consumption intention of organic food, subsequently predicting actual consumption. Hence, addressing these psychological factors is crucial in promoting sustainable food choices among Malaysian adults.